2009
DOI: 10.1111/j.1460-9568.2009.06946.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐type plasminogen activator‐plasmin‐BDNF modulate glutamate‐induced phase‐shifts of the mouse suprachiasmatic circadian clock in vitro

Abstract: The mammalian circadian clock in the suprachiasmatic nucleus (SCN) maintains environmental synchrony through light signals transmitted by glutamate released from retinal ganglion terminals. Brain-derived neurotrophic factor (BDNF) is required for light/glutamate to reset the clock. In the hippocampus, BDNF is activated by the extracellular protease, plasmin, which is produced from plasminogen by tissue-type plasminogen activator (tPA). We provide data showing expression of proteins from the plasminogen activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 70 publications
1
47
0
Order By: Relevance
“…Microarray studies have shown that tPA, plasminogen, and plasminogen-activator-inhibitor-1 (PAI-1) mRNAs are expressed in the SCN, with tPA and PAI-1 mRNAs showing rhythmic expression (Panda et al 2002). tPA-plasminogen-BDNF modulates glutamateinduced phase-shifts of the circadian clock in cultured suprachiasmatic neurons (Mou et al 2009). The SCN is anatomically and functionally organized into two subdivisions: a core that lies adjacent to the optic chiasm, and a shell that surrounds the core in its dorsomedial portion.…”
Section: Plasminogen In the Hypothalamusmentioning
confidence: 98%
“…Microarray studies have shown that tPA, plasminogen, and plasminogen-activator-inhibitor-1 (PAI-1) mRNAs are expressed in the SCN, with tPA and PAI-1 mRNAs showing rhythmic expression (Panda et al 2002). tPA-plasminogen-BDNF modulates glutamateinduced phase-shifts of the circadian clock in cultured suprachiasmatic neurons (Mou et al 2009). The SCN is anatomically and functionally organized into two subdivisions: a core that lies adjacent to the optic chiasm, and a shell that surrounds the core in its dorsomedial portion.…”
Section: Plasminogen In the Hypothalamusmentioning
confidence: 98%
“…56 Increased levels of PAI-1 may also be linked to reduced neurotrophic support in the brain of schizophrenia patients, because PAI-1 is involved in brainderived neurotrophic factor maturation in the hippocampus. 57 Nevertheless, further studies are required to investigate the exact impact of elevated PAI-1 on brain function.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were euthanized 1 or 2 h following social defeat or empty cage exposure, and tissue punches were collected bilaterally from the BLA/CeA. Western blot assays for proBDNF and mBDNF were performed as previously described (Mou et al 2009). A detailed Methods section is provided as Supplemental Material.…”
mentioning
confidence: 99%